Restrukturisasi daging sandung lamur menjadi patties burger menggunakan enzim transglutaminase - Norma Rahma Susanti; Santi Dwi Astuti; Isti Handayani (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The processing of beef brisket into patties is one of a approach to increase the value of low-quality meat. Transglutaminase (TGase) enzyme was used to restructure the beef brisket more effective. This aim of this research was to determine the effect of different mechanical treatments and concentrations of TGase on the physical and chemical characteristics of brisket patties. The beef brisket was elaborated with mechanical treatment (milled and chopped) and different levels of the TGase (0.5%, 0.75%, and 1%). The products were distinguished by their physical properties (hardness, cohesiveness, springiness, chewiness, water holding capacity) and chemical properties (ash, protein, fat, water activity). The data were analyzed using 2x3 factorial completely randomized design (CRD) by GLM-ANOVA model of SPSS software with 4 repetitions. A significant increased (P0.05) was observed for the mechanical treatment (hardness, springiness, chewiness, WHC) and differences in TGase concentrations (cohesiveness, WHC). Regarding the proximate composition (ash, protein and fat), no significant differences (P0.05) were found. The effectiveness index analysis showed a combination of milled brisket with the addition of 1% TGase could be an efficient method to increase the physical properties.